UNIT 1G.7 Rapid Screening of the Endodermal Differentiation Potential of Human Pluripotent Stem Cells. (15th November 2017) - Siller, Richard; Sullivan, Gareth J.
Abstract: Human pluripotent stem cells (hPSCs) hold tremendous promise for regenerative medicine, disease modeling, toxicology screening, and developmental biology. These applications are hindered due to inherent differences in differentiation potential observed among different hPSC lines. This is particularly true for the differentiation of hPSCs toward the endodermal lineage. Several groups have developed methods to screen hPSCs for their endodermal differentiation potential (EP). Particularly notable studies include (i) the use of WNT3A expression as a predictive biomarker, (ii) an embryoid body–based screen, and (iii) a transcriptomics‐based approach. We recently developed a rapid screen to access the EP of hPSCs solely based on morphological analysis. The screen takes 4 days to perform and yields results that are easy to interpret. As the screen is based on our recently developed small molecule protocol for hepatocyte like cell (HLC) differentiation of hPSCs, this method is extremely cost‐effective compared to the aforementioned approaches. © 2017 by John Wiley & Sons, Inc.